Stigma, anxiety, depression, social support and quality of life in young women with breast cancer undergoing chemotherapy: a predictive model - Wenzhen, Tang (2024)
Young women diagnosed with breast cancer (BC) are increasing annually, and they are prone to mental health problems, which significantly reduce their quality of life (QoL). Social support is crucial for enhancing the QoL in patients with BC. However, the relationship between stigma, anxiety, depression, social support, and QoL in young women with BC undergoing chemotherapy remains unclear. This study aims to examine the relationship between stigma, anxiety, depression, social support, and QoL among young women with BC undergoing chemotherapy. This cross-sectional study was done in the First Affiliated Hospital of Guangxi Medical University, China, from December 2022 to October 2023. The research instruments were the Functional Assessment of Cancer Therapy-Breast (FACT-B), the Social Support Rating Scale (SSRS), the Social Impact Scale (SIS), and the Hospital Anxiety Depression Scale (HADS). SPSS 26.0 and AMOS28.0 software were used for statistical analyses. Data were analysed using descriptive, univariate, correlation analysis, structural equation model (SEM) and multiple linear regression (MLR). 196 women with BC aged ≤ 40 were included in the study. The mean QoL score of participants was at a moderate level, 98.01 (SD = 16.97). The findings indicated participants' QoL was associated with education level (p = 0.010), residence (p = 0.004), surgery type (p = 0.021), current chemotherapy cycle (p = 0.002) and postoperative time (p = 0.020). Stigma (r = −0.590), anxiety (r = −0.344), and depression (r = −0.236) were negatively correlated with the QoL among young women with BC. However, there was a positive correlation between social support and QoL (r = 0.416). In addition, social support significantly mediated the impact of stigma (β = −0.214, p = 0.016) and depression (β = −0.084, p = 0.030) on the QoL. However, social support did not significantly mediate the relationship between anxiety and QoL (β = 0.054, p = 0.105). 41.3% of the variance in QoL among young women with BC was explained by stigma, anxiety, and social support. In conclusion, a significant interaction exists among stigma, social support, anxiety, depression, and QoL in young women with BC undergoing chemotherapy. This finding highlights the importance of assessing the psychological challenges faced by young women with BC as part of routine care. Furthermore, it underscores the need for the future development and implementation of mental health support programs tailored to young women with BC undergoing chemotherapy.